Linkages between Solo-Selo-Borobudur as the Jawa Tengah Provincial tourism strategic area. Issue 1 (April 2021) - Pinanigas, A J; Fatimah, E; Ramadhani, A
Abstract: Provincial Strategic Areas (PSA) are areas prioritized in spatial planning because of their significantly influence on economy, socio-culture, or environment perspectives. Solo-Selo-Borobudur is designed as one of Central Java PSAs. This PSA is expected to become a tourism corridor area and the sub areas within the PSA are expected to be equally developed and integrated as a single entity. In fact, there is a significant difference in the number of tourists visiting the three areas, which indicates an imbalance in the level of development. This study aims to examine the level of development of each sub-area and to identify the level of linkages between them in terms of their activities. The scoring method was used to identify the level of development in terms of attraction, accessibility, amenities and ancillary services (4A) aspects. A questionnaire survey was also conducted to explore tourism behaviour in order to identify linkages between the three tourism areas. The data obtained is analyzed by using spatial descriptive method. The result of this study shows the level of development of Solo and Borobudur tourism sub-areas can be classified high level, while Selo is still low (undeveloped). The study also found that the linkage between Solo - Borobudur tourism activities was stronger than between Solo - Selo and Selo - Borobudur. As the PSA, the linkage between the three tourism areas is still low. The findings are expected to be related to differences in the level of development between the three areas.